Analisis Usaha Penggemukan Sapi Bali di Kelompok Tani Bero Sembada Kecamatan Laen Mane Kabupaten Malaka - Maria Fatima Bere (JAS, 2019)
This research was conducted in Laen Mane Subdistrict, Malacca District, East Nusa Tenggara Province for one month. The purpose of this study was to analyze the Bali Cattle Fattening Farmer Group Bero Sembada Farmer, Laen Mane District, Malacca District. The method used is purposive sampling with interviews (interview respondents) directly using questionnaire aids and direct observation of the object under study. The variables studied were the characteristics of respondents, acceptance and income of farmer groups. It was concluded that the education level of the Bero Sembada farmer group members was on average an elementary school (84%), with a productive age level and a fairly long experience of raising livestock with dependents ranging from 5-7 people. The average income of farmers in the business of fattening Bali cattle in the Bero Sembada farmer group on a 2-tailed fattening scale provides the best average income with an income of Rp. 8,800,337, - (Rp. 4,400,169, -) per year or a month's income is equivalent to Rp. 733,361 (Rp.366,681). The business is feasible to run as seen from the B / C ratio value of 1.23 which means> 1 so that it is financially feasible on a 2-tailed business scale.